Clinical predictors and outcomes of ST-elevation myocardial infarction related cardiogenic shock in the Asian population - Djohan, Andie Hartanto; Evangelista, Lauren Kay Mance; Chan, Koo-Hui; Lin, Weiqin; Adinath, Anand Ambhore; Kua, Jie Li; Sim, Hui Wen; Chan, Mark Y.; Ng, Gavin; Cherian, Robin; Wong, Raymond C.C.; Lee, Chi-Hang; et al. (International journal of cardiology. Heart & vasculature, 2024)
Cardiogenic shock (CS) complicating myocardial infarction is associated with poor outcomes. Data among Asian populations are scarce. We aimed to investigate the long-term outcomes, prognostic factors, and predictors of CS among Asian ST elevation myocardial infarction (STEMI) patients. This was a retrospective cohort study of consecutive patients undergoing primary percutaneous coronary intervention (PPCI) for STEMI within our regional STEMI network between 2015 and 2019. The long-term outcomes of those with and without CS were compared. Clinical predictors of outcomes and development of CS were investigated. A total of 1791 patients who underwent PPCI were included. Patients completed at least 2 years’ follow-up with a median follow-up period of 2.6 years (IQR 1.0, 3,9). Overall, 208/1791 (11.6 %) STEMI patients developed CS. These patients were older (61.1 ± 12.5 vs 57.8 ± 12.2, P < 0.001) and mostly men (87.0 %). All-cause mortality (59.9 % vs 4.7 % P < 0.001), cardiac mortality (43.8 % vs 2.2 %, P < 0.001) and major adverse cardiovascular events (MACE) was significantly higher in the CS group (59.1 % vs 14.0 %, P < 0.001). Independent predictors of survival were higher index LVEF (adjusted hazards ratio [aHR] 0.967, 95 %CI 0.951–0.984, p < 0.001) and higher arterial pH at onset of shock (aHR 0.750, 0.626–0.897, p = 0.002). Increased serum lactate concentration independently predicts poor prognosis (aHR 1.084, 95 % CI 1.046–1.124, p < 0.001). In Asian STEMI patients who underwent PPCI, CS was associated with poor outcomes. Higher LVEF on index admission was associated with better outcomes; while lactic acidosis independently predicted mortality.